How to Build a Hug Temple Grandin and Her Amazing Squeeze Machine - Guglielmo, Amy; Tourville, Jacqueline; Potter, Giselle (New York, New York Atheneum Books for Young Readers, 2018)
Presents the story of Grandin's "squeeze machine," describing her childhood love of building and design, as well as her sensitivities.
Age 4-8.
K to Grade 3.
Accelerated Reader AR
Lexile
114121
Keywords: Grandin, Temple -- Juvenile literature; Animal scientists -- United States; Autism spectrum disorders -- Treatment; Inventions; Animal scientists; United States